Early postoperative ERAS compliance predicts decreased length of stay and complications following liver resection. Issue 9 (September 2022) - Burchard, Paul R.; Dave, Yatee A.; Loria, Anthony P.; Parikh, Neilesh B.; Pineda-Solis, Karen; Ruffolo, Luis I.; Strawderman, Myla; Schoeniger, Luke O.; Galka, Eva; Tomiyama, Koji; Orloff, Mark S.; Carpizo, Darren R.; et al.
Abstract: Background: Enhanced recovery after surgery (ERAS) components for liver resection lack standardization and compliance. We evaluated our ERAS protocol and describe the association of postoperative ERAS compliance with length of stay (LOS) and complications. Methods: We retrospectively reviewed patients undergoing liver resection at our institution from 2016 to 2020. Pre- and post-ERAS outcomes and compliance at 72 h were compared with LOS and complications. LOS beyond 72 h was defined as LOS72. Results: 210 patients were included. Post-ERAS patients had significantly shorter LOS (5.1 vs. 7.3 days, p = 0.0014) with no difference in 30-day mortality, morbidity, or readmissions. ERAS components associated with shorter LOS72 were regular diet (HR 1.73), fluid discontinuation (HR 1.63), drain removal (HR 1.94), multimodal and oral analgesia (HR 1.51), and ambulation >100 ft (HR 2.23). LOS72 was 1-day for ≥9 ERAS component compliance, 4-days for 6–8 components, and 6-days for <6 components. 30-day complication rates for patients with ≥9 components by postoperative day 3 (POD3) were significantly lower than those with 6–8 (12 vs 32%). Conclusion: ERAS decreases LOS after liver resection. Nutritional advancement, drain discontinuation, multimodal and oral analgesia, and ambulation >100 ft by POD3 are associated with decreased LOS72. Achieving ≥6 components by POD3 predicts decreased LOS72 and complications.